Hypertension: New perspective on its definition and clinical management by bedtime therapy substantially reduces cardiovascular disease risk. (25th February 2018) - Hermida, Ramón C.; Ayala, Diana E.; Fernández, José R.; Mojón, Artemio; Smolensky, Michael H.
Abstract: Diagnosis of hypertension—elevated blood pressure (BP) associated with increased cardiovascular disease (CVD) risk—and its management for decades have been based primarily on single time‐of‐day office BP measurements (OBPM) assumed representative of systolic (SBP) and diastolic BP (DBP) during the entire 24‐hours span. Around‐the‐clock ambulatory blood pressure monitoring (ABPM), however, reveals BP undergoes 24‐hours patterning characterized in normotensives and uncomplicated hypertensives by striking morning‐time rise, 2 daytime peaks—one ~2‐3 hours after awakening and the other early evening, small midafternoon nadir and 10‐20% decline (BP dipping) in the asleep BP mean relative to the wake‐time BP mean. A growing number of outcome trials substantiate correlation between BP and target organ damage, vascular and other risks is greater for the ABPM‐derived asleep BP mean, independent and stronger predictor of CVD risk, than daytime OBPM or ABPM‐derived awake BP. Additionally, bedtime hypertension chronotherapy, that is, ingestion of ≥1 conventional hypertension medications at bedtime to achieve efficient attenuation of asleep BP, better reduces total CVD events by 61% and major events (CVD death, myocardial infarction, ischaemic and haemorrhagic stroke) by 67%—even in more vulnerable chronic kidney disease, diabetes and resistant hypertension patients—than customary on‐awaking therapy that targets wake‐time BP. Such findings of around‐the‐clock ABPM and bedtime hypertension outcome trials, consistently indicating greater importance of asleep BP than daytime OBPM or ambulatory awake BP, call for a new definition of true arterial hypertension plus modern approaches for its diagnosis and management.